Exploring Junior High School Students’ Perceptions of Digital Posters as Visual Learning Media in English Language Teaching - Rizky Hidayatullah; Choirudin Choirudin; Dian Anggraini; Andi Mappewali; Sarirotus Sa’diyah; Ria Wulandari (CV. Creative Tugu Pena, 2025)
This study investigated students’ perceptions of the use of digital posters in English language learning at the junior high school level. The integration of digital media in English Language Teaching (ELT) is considered essential to enhance students’ engagement, motivation, and understanding of learning materials. This research employed a qualitative descriptive approach to explore students’ perceptions from cognitive, affective, visual, technical, and learning aspects. The participants were 51 students of SMP Negeri 5 Metro who had experienced learning English using digital posters. Data were collected through questionnaires, classroom observations, and interviews with the English Club supervisor as supporting data. The findings revealed that students generally demonstrated positive. perceptions toward the use of digital posters. From the cognitive aspect, students perceived that digital posters helped them understand and remember English vocabulary and materials more easily. Affectively, digital posters increased students’ motivation, interest, and enjoyment in learning English. Visually, the design elements such as colors, images, and layout were considered attractive and supportive of learning. From the technical aspect, most students reported that digital posters were easy to use with minimal technical difficulties. Furthermore, students perceived that digital posters contributed to more effective and interactive English learning. These findings suggest that digital posters can serve as a supportive learning medium in English classrooms when appropriately designed and implemented.